A new species of the genus Cloeon Leach, 1815 from China (Ephemeroptera: Baetidae). Issue 1 (13th May 2021) - Tong, Xiaoli; Dudgeon, David
Abstract: Cloeon micki sp. n., a new species of baetid mayfly from China is described and illustrated based on larval and imaginal stages associated by laboratory rearing. The new species is characterised by the presence of a dark brown or dark purple elliptical marking on abdominal tergites II and V, which readily distinguishes it from other members of the genus Cloeon Leach, 1815 . The known distribution of the new species is Hong Kong, Guangdong and Henan provinces. http://www.zoobank.org/urn:lsid:zoobank.org:pub:7ED660DD-513B-4A0E-AC68-877D7DC5E7D4